Essential Oil Analysis and Isolation of Coumarins and Flavonol Glycosides of Ferulago angulata (Schltdl.) Boiss. Fruits - Hedieh Farokhi-Firoozi; Mahtab Rahavi; Morteza Pirali-Hamedani; Abbas Hadjiakhundi; Mohammad-Reza Delnavazi (Tabriz University of Medical Sciences, 2021)
Background: Ferulago angulata (Schltdl.) Boiss. is a herbaceous perennial plant distributed in Iran, Turkey and Iraq. The aromatic aerial parts of this plant are commonly used as antiseptic, sedative, wound healing, analgesic and food additive. Methods: Column chromatography on silica gel (normal phase and RP-18) and Sephadex LH-20, along with recrystallization method were applied to isolation of the phytochemicals extracted from F. angulata fruits. The structures of the isolated compounds were characterized by 1H-NMR and 13C-NMR spectral analysis. Chemical composition of the fruits essential oil obtained by hydrodistillation (HD) and steam distillation (SD) methods were also analyzed using GC-MS technique. Results: Six coumarin derivatives; suberosin (1), isoimperatorin (2), imperatorin (3), bergapten (4), tamarin (5) and suberenol (6), a monoterpene glycoside; verbenone-5-O-β-D-glucopyranoside (7), together with five flavonol-3-O-glycosides; isorhamnetin-3-O-rutinoside (narcissin) (8), kaempferol-3-O-rutinoside (nicotiflorin) (9), quercetin-3-O-rutinoside (rutin) (10), isorhamnetin-3-O-β-D-glucuronide (11), isorhamnetin-3-O-β-D-glucopyranoside (12) were isolated from F. angulata fruits. Essential oil extraction using HD and SD methods afforded colorless oils in 4.1 and 1.8% (v/w) yields, respectively. A total of 28 compounds were identified in essential oils, of which (Z)-β-ocimene (HD; 48.97%, SD; 50.02%), α-pinene (HD; 21.32%, SD; 23.06%) and allo-ocimene (HD; 6.98%, SD; 5.61%) were the main compounds. Conclusion: This study introduces F. angulata fruits as a new source of coumarin derivatives and flavonoid glycosides. The presence of these compounds with known biological properties provides more medicinal potentials for the fruits of F. angulata. The present study also reports hydrodistillation, as an efficient method for extraction of essential oil from these aromatic fruits.